Reciprocal Equilibria in Link Formation Games - Hannu Salonen (Aboa Centre for Economics (ACE), 2014)
We study non-cooperative link formation games in which players have to decide how much to invest in relationships with other players. A link between two players is formed, if and only if both make a positive investment. The cost of forming a link can be interpreted as the opportunity cost of privacy. We analyze the existence of pure strategy equilibria and the resulting network structures with tractable specifications of utility functions. Sufficient conditions for the existence of reciprocal equilibria are given and the corresponding network structure is analyzed. Pareto optimal and strongly stable network structures are studied. It turns out that such networks are often complete.
Keywords: C72; D43; 330; link formation games; reciprocal equilibrium; complete network